Asymmetric Total Synthesis of Vindoline - Kato, Daisuke (2010)
A concise asymmetric total synthesis of (−)-vindoline (1) is detailed based on a tandem intramolecular [4+2]/[3+2] cycloaddition cascade of a 1,3,4-oxadiazole inspired by the natural product structure, in which the tether linking the initiating dienophile and oxadiazole bears a chiral substituent that controls the facial selectivity of the initiating Diels–Alder reaction and sets absolute stereochemistry of the remaining six stereocenters in the cascade cycloadduct. This key reaction introduces three rings and four C–C bonds central to the pentacyclic ring system setting all six stereocenters and introducing essentially all the functionality found in the natural product in a single step. Implementation of the approach also required the development of a unique ring expansion reaction to provide a 6-membered ring suitably functionalized for introduction of the Δ(6,7)-double bond found in the core structure of vindoline and defined our use of a protected hydroxymethyl group as the substituent used to control the stereochemical course of the cycloaddition cascade.